Resistencia a enfermedades bacterianas - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
During 1984 a collaborative research effort between CIAT and the National Vegetable Research Station (Wellesbourne, England) was started to broaden the knowledge of halo blight caused by Pseudomonas phaseolicola. Isolates of the halo blight pathogen were collected from bean growing areas of Latin America and Africa. Results of preliminary pathogenicity tests show the apparent occurrence of unknown variability in pathogenicity of P. phaseolicola different from the known races 2 and 3. Additionally, 230 bean cv. were evaluated for their reaction to halo blight under field conditions in Popayan. Of these, 147 were selected as resistant and 55 as intermediate. In another series of trials, a cross of PI 319443 x G 40111 was made to study the inheritance of common bacterial blight (Xanthomonas phaseoli) resistance from the resistant Phaseolus acutifolius parent. Significant dominance and additive genetic effects were observed, and 3 genetic factors are believed to control the resistance. A 2nd major breeding project in common bacterial blight resistance was conducted to recombine intermediate levels of resistance into black-seeded cv. having commercial grain type, high yield potential, and resistance to BCMV. (CIAT)